My Interactive Digital Book (MyID Book) V2.0 / Muhammad Zikrylah Arfan Zulkifli … [et al.] - Zulkifli, Muhammad Zikrylah Arfan; Syed Salim, Syed Mohd Albanna; Wan Mohamad, Wan Nur Intan Qistina; Jamal Abdillah, Nur Izzati Batrisyia; Syed Mohd Albanna, Sharifah Ainun Mutmainnah (Faculty of Computer and Mathematical Sciences, 2021)
Reading books is the best way to enrich our vocabulary but the reading materials are too rigid with paper, picture and words. Games and gamification basis are the best method to attract students in learning with when offline and online resources are nicely blend under one roof. A book full with interactive activities is the best idea to counter most of the problems listed. Because of that reason, we build an android mobile app called My Interactive Digital Book (MylD book) to attract students to learn English in a super fun way. MylD book is focusing on vocabulary of zoo animals in colourful characters, interactive online and offline games, informative contents, language arts activities, Augmented reality and many more exciting features to explore! Download the full version here:bit.ly/myidbook